2002
DOI: 10.1096/fj.01-0792fje
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged unloading of rat soleus muscle causes distinct adaptations of the gene profile

Abstract: Using commercially available microarray technology, we investigated a series of transcriptional adaptations caused by atrophy of rat m. soleus due to 35 days of hindlimb suspension. We detected 395 out of 1,200 tested transcripts, which reflected 1%-5% of totally expressed genes. From various cellular functional pathways, we detected multiple genes that spanned a 200-fold range of gene expression levels. Statistical analysis combining L1 regression with the sign test based on the conservative Bonferroni correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 122 publications
(179 reference statements)
5
95
3
Order By: Relevance
“…After denervation of the diaphragm, an increased phosphorylation level of S6 ribosomal protein was reported previously (70). Several recent studies also showed an upregulation of a number of ribosomal proteins and initiation and elongation factors in skeletal muscles undergoing atrophy due to immobilization and unloading (7,85,86,96) as well as fasting, uremia, diabetes, and cachexia (62). The current microarray study is in good agreement with previous publications (16,55,56) in the detection of increased expression of the "developmental" isoform (eEF1A-1) of elongation factor-1A (eEF1A) in EDL muscles after denervation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After denervation of the diaphragm, an increased phosphorylation level of S6 ribosomal protein was reported previously (70). Several recent studies also showed an upregulation of a number of ribosomal proteins and initiation and elongation factors in skeletal muscles undergoing atrophy due to immobilization and unloading (7,85,86,96) as well as fasting, uremia, diabetes, and cachexia (62). The current microarray study is in good agreement with previous publications (16,55,56) in the detection of increased expression of the "developmental" isoform (eEF1A-1) of elongation factor-1A (eEF1A) in EDL muscles after denervation.…”
Section: Discussionsupporting
confidence: 91%
“…*Significant difference compared with the expression levels in control EDL muscles at p(t) Յ 0.01. #Significant difference compared with the expression levels in stimulated-denervated EDL muscles at p(t) Յ 0.01. alloproteinases has been reported in muscles in response to unloading (96) and during regeneration (38). Coordinate upregulation in the expression of two serine proteases, tonin and kallikrein, after denervation of EDL muscles may have considerable physiological significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of MMPs that is upregulated and the time frame of this upregulation depend, a great deal, on the model used. Immobilization or unloading, that result in muscle fiber atrophy, induce upregulation of both MMP-2 and MMP-9 and downregulation of TIMPs (Berthon et al, 2007;Giannelli et al, 2005;Reznick et al, 2003;Stevenson et al, 2003;Wittwer et al, 2002) (Berthon et al, 2007;Giannelli et al, 2005;Reznick et al, 2003;Stevenson et al, 2003;Wittwer et al, 2002 ) but only MMP-2 is active (Liu et al, 2010). Whereas a single bout of degeneration-regeneration, induced by experimental injury to the muscle, also results in upregulation of these two proteases but the time frame and intensity differ according to the type/extent of injury (Ferre et al, 2007;Frisdal et al, 2000;Kherif et al, 1999).…”
Section: Matrix Metalloproteinases In Remodeling Musclesmentioning
confidence: 99%
“…Functionally overloading the rat soleus muscle for 3 days alters gene expression for immune function, inflammation, and cell cycle regulation (9). Brief periods of muscle unloading initiate signaling that decreases muscle mass that includes a decrease in protein synthesis (26) and satellite cell proliferation (11).Increasing or decreasing muscle loading for extended periods can reduce the soleus muscle's ability to oxidize longchain fatty acids (14,41,49) and is likely related to a reduced expression of 3-hydroxyacyl-CoA dehydrogenase (41), fatty acid transport proteins (9, 49), and fatty acid binding proteins (49). It has been shown that functional overload can decrease many markers related to glycogen metabolism in both slow and fast muscles (4, 35).…”
mentioning
confidence: 99%
“…Increasing or decreasing muscle loading for extended periods can reduce the soleus muscle's ability to oxidize longchain fatty acids (14,41,49) and is likely related to a reduced expression of 3-hydroxyacyl-CoA dehydrogenase (41), fatty acid transport proteins (9,49), and fatty acid binding proteins (49). It has been shown that functional overload can decrease many markers related to glycogen metabolism in both slow and fast muscles (4,35).…”
mentioning
confidence: 99%